Remote-focussing for volumetric imaging in a contactless and label-free neurosurgical microscope - Cui, J; Turcotte, R; Hampson, K; Emptage, NJ; Booth, MJ (Optica Publishing Group, 2020)
We present a compact and contactless reflectance confocal neurosurgical microscope that allows remote-focussing via a deformable mirror for volumetric imaging. Wavefront analysis was performed and remote-focussing was demonstrated in mouse calvaria.